(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2022)
Introduction: To find out the audiometric outcome after stapedotomy patients with clinical diagnosis of otosclerosis. Methods: This prospective observational study was performed in a total of 142 patients diagnosed with primary Otosclerosis, who underwent Stapedotomy at the Department of ENT & Head-Neck Surgery, Combined Military Hospital, Dhaka between January 2013 to January 2018. All patients were evaluated as per the candidacy criteria for stapedotomy and selected patients underwent surgery during the study period and were followed up for a period of 12 months in the Otology clinic. Pre-operative and Post-operative audiometric evaluation were done using conventional pure tone audiometry with standard calibrations. Post-operative audiometry was performed at 03 month, 06 month and 12 month. Results: Overall, the frequency specific pre-operative mean average Air-Bone gap was 51.6 dB at 500Hz, 35.7 dB at 1000 Hz, 40.5 dB at 2000 Hz, 38.9 dB at 4000 Hz and the frequency specific postoperative mean average Air- Bone Gap closure was achieved by 28.1 dB at 500Hz, 30.3 dB at 1000 Hz, 12.5 dB at 2000 Hz, 10.8 dB at 4000 Hz, by the time of 1 years of follow up. The difference was statistically significant (p<0.05) between pre-operative Air-Bone gap and post operative Air-Bone gap. After the surgery 88.7% tinnitus patients reported improvement and 11.3 % noted no change in tinnitus. Postoperative sensorineural hearing loss (SNHL) was seen in 1.4 %, failure rate was found 3.8% and 1.4% patients developed post-operative persistent vertigo. Conclusion: Most of the audiometric Results reveal excellent hearing improvement after stapedectomy surgery and worsened bone conduction (postoperative threshold shifts) for primary otosclerosis. It is safe and successful procedure providing long-term hearing expansion in primary otosclerosis with minimum failure rate. J Bangladesh Coll Phys Surg 2022; 40: 116-120